Patient safety culture in out-of-hours primary care services in the Netherlands: a cross-sectional survey - Smits, Marleen; Keizer, Ellen; Giesen, Paul; Deilkås, Ellen C Tveter; Hofoss, Dag; Bondevik, Gunnar Tschudi
Objective: To examine patient safety culture in Dutch out-of-hours primary care using the safety attitudes questionnaire (SAQ) which includes five factors: teamwork climate, safety climate, job satisfaction, perceptions of management and communication openness. Design: Cross-sectional observational study using an anonymous web-survey. Setting Sixteen out-of-hours general practitioner (GP) cooperatives and two call centers in the Netherlands. Subjects Primary healthcare providers in out-of-hours services. Main outcome measures Mean scores on patient safety culture factors; association between patient safety culture and profession, gender, age, and working experience. Results: Overall response rate was 43%. A total of 784 respondents were included; mainly GPs (N = 470) and triage nurses (N = 189). The healthcare providers were most positive about teamwork climate and job satisfaction, and less about communication openness and safety climate. The largest variation between clinics was found on safety climate; the lowest on teamwork climate. Triage nurses scored significantly higher than GPs on each of the five patient safety factors. Older healthcare providers scored significantly higher than younger on safety climate and perceptions of management. More working experience was positively related to higher teamwork climate and communication openness. Gender was not associated with any of the patient safety factors. Conclusions: Our study showed that healthcare providers perceive patient safety culture in Dutch GP cooperatives positively, but there are differences related to the respondents’ profession, age and working experience. Recommendations for future studies are to examine reasons for these differences, to examine the effects of interventions to improve safety culture and to make international comparisons of safety culture. Key Points Creating a positive patient safety culture is assumed to be a prerequisite for quality and safety. We found that: • healthcare providers in Dutch GP cooperatives perceive patient ...